Embattled women: The effects of social displacement caused by armed conflict on the reproductive health of women internal refugees in Northern Mindanao, Philippines - Coronel, Dennis B. (Animo Repository, 2003)
The long-standing armed conflict between the military and the Muslim separatist groups in Northern Mindanao, has resulted in the tremendous damage to public infrastructure and the destruction of the social fabric and the lives of countless civilians. Where conflict is long and highly sporadic over short periods of seeming peace, population displacement and evacuations are also numerous, short-term, and always in an emergency mode of response catering only to immediate needs. The present study investigated and described the effects of social displacement on the reproductive health of women internal refugees in one of the provinces in Northern Mindanao*. Particularly, it looked into the women’s health status under such condition, and their perceived reproductive health needs. The study also presented the different actions of women to address these conditions, and the role that the Local Government Unit (LGU) and other assistance groups have played to facilitate and assist the women in realizing their actions. This qualitative study, which utilized an exploratory-descriptive research design, employed a triangulation of research methods, namely: participant observation, key informant in-depth interview, and document review for data collection. The key informant sample consisted of 20 purposively selected women internal refugees who were of reproductive age (15-45), had at least one child, and are residents of the two hardest hit communities of the rebel attacks in the province. Participant observation was facilitated through an on-site volunteer work in relief operations with the local DSWD, the media, the military group, and NGOs This study investigates and describes the effects of social displacement on the reproductive health of women internal refugees in one of the provinces of Northern Mindanao (The real names and locations of the communities and that of the province have been omitted and are here fictitiously represented for ethical considerations). This qualitative study, which utilized an exploratory-descriptive research design, employed a triangulation of research methods, namely: participant observation, key informant in-depth interview, and document review for data collection. The key informant sample consisted of 20 purposively selected women internal refugees who were of reproductive age (15-45), had at least one child, and are residents of the two hardest hit communities of the rebel attacks in the province. Participant observation was facilitated through an on-site volunteer work in relief operations with the local Department of Social Welfare and Development (DSWD), the media, the military group, and Non-Government Units (NGOs). The study has shown that social displacement affects women's reproductive health in at least two ways: (1) through the exacerbation of pre-existing RH problems, and (2) the creation of new social and living conditions that lead to the emergence of new RH problems. This study also considered two other aspects that proved pertinent as they provided basis for understanding women's RH status and their actions to address their RH problems and needs. These aspects were: (1) the effects of social displacement on the over-all physical condition, mental health and emotional well-being of women and (2) the effects of social displacement on men and on gender relations at the evacuation center, and how this has affected women. Notably, as women's RH problems and needs increased, there was also a diminishing capacity on the part of the local health care units to respond adequately and effectively as a result of tension and disrupted social networks. It was also revealed that local health care systems (RHU and BHS) have long been buckling under the strain of insufficient human resources, supplies and even political will, and thus in the context of emergency and massive social displacement, found themselves direly wanting and inadequate. Women's actions were also shown to be heavily dependent on their husband and intimate male partner, as well as on outside structures such as the Local Government Units (LGU), DSWD and NGOs. The strong sense of exclusive in-group affiliation, which in itself is a coping mechanism and a strategy for survival, also has an adverse effect towards this end. This study also revealed a pattern of dependency on assistance groups and the misappropriation of goods and services that do not answer the real RH needs of women during displacement. There had been no efforts for community development, nor any initiative to build on human resources of the displaced population. In the end, the usual approach to immediate relief operations had served to undermine local capacity and consequently diminished women's health-supporting activities. Indeed, as this study has revealed, there is a dire need to understand the various attractors that serve to influence women's coping strategies and perceptions in the context of displacement,--such as gender relations, power politics and socio-cultural nuances, and how all these are compounded to undermine their reproductive health status and needs. This study further pointed out the necessity for such a perspective if the intention is to come up with a truly comprehensive, culturally appropriate set of responses to women's reproductive health needs during displacement.